Grating-coupled plasmonic sensor for sucrose sensing fabricated using optical fiber-based interference lithography (OFIL) system - Pae, Jian Yi (2020)
A grating-coupled plasmonic sensor for sucrose sensing was fabricated and experimentally validated in the spectral interrogation mode. The grating structures were fabricated on a silicon wafer using an optical fiber-based interference lithography (OFIL) system. The system can be easily reconfigured to write 1D grating features with a periodicity ranging from 514 nm to 1,646 nm. The patterned area can also be controlled from 5 mm down to 0.6 mm for energy efficient, device scale fabrication. The results demonstrated the potential of using the OFIL system as a highly versatile and low-cost method to fabricate grating-coupled plasmonic sensors for healthcare applications.